Managing common mental health disorders in healthcare workers. (14th May 2019) - See, B; Juszczyk, D; Parsons, V; Smedley, J; Gilworth, G; Madan, I
Abstract: Background: Approximately a quarter of sickness absence in the UK National Health Service (NHS) is attributed to common mental health disorders (CMHDs). This is costly to the NHS and impacts on patient care and staff morale. Little is known about the occupational health (OH) management of NHS staff who take sick leave for CMHDs. Aims: To explore the current OH management of NHS staff on sick leave for CMHDs. Methods: We invited providers of NHS OH services identified from the NHS Health at Work Network and Commercial OH Providers Association to complete a survey on the management of employees off work because of CMHDs. Analysis involved descriptive statistics and content analysis. Results: Forty-nine (39%) of the 126 OH departments approached responded. The majority (98%) had an organizational sickness absence policy that included triggers for referral for staff absent with CMHDs. In 63%, referral occurred 8–28 days after the onset of absence; in 92%, the consultation was completed by an OH nurse or OH physician. Content of the first consultation often included assessment of symptoms and medication for CMHDs. Case management and regular reviews were least commonly used despite evidence on their effectiveness in supporting return to work. All providers offered some support for managers of staff with CMHDs. Conclusion: Variation existed between providers of NHS OH services in the timing of referrals, use of case management and regular reviews for staff with CMHDs. Our findings suggest that current evidence-based guidance on interventions to improve return to work is not being implemented consistently.